2017
DOI: 10.1200/jco.2016.68.3300
|View full text |Cite
|
Sign up to set email alerts
|

E1308: Phase II Trial of Induction Chemotherapy Followed by Reduced-Dose Radiation and Weekly Cetuximab in Patients With HPV-Associated Resectable Squamous Cell Carcinoma of the Oropharynx— ECOG-ACRIN Cancer Research Group

Abstract: Human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC) is treatment-responsive. Definitive chemoradiation results in high cure rates but causes long-term toxicity and may represent overtreatment of some patients. This phase II trial evaluated whether complete clinical response (cCR) to induction chemotherapy (IC) could select patients with HPVassociated OPSCC for reduced radiation dose as a means of sparing late sequelae. MethodsPatients with HPV16 and/or p16-positive, stage III-IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
338
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 404 publications
(347 citation statements)
references
References 29 publications
6
338
1
2
Order By: Relevance
“…42,43,50 The ECOG-ACRIN phase II E1308 trial, in which patients with stage III-IV HPV16 and/or p16-positive oropharyngeal cancer (N=80) received induction chemotherapy followed by reduced-dose RT and weekly cetuximab, recently reported results showing that RT deintensification may result in equivalent or similar responses in selected patients compared with fulldose RT. 51 The relationship between HPV and other prognostic or predictive factors such as smoking history and stage has been investigated. 52,53 For example, analyses of patients with oropharyngeal cancer who were enrolled in RTOG 9003 or 0129 (n=165) showed that smoking was associated with decreased OS and PFS, regardless of p16 status.…”
Section: Hpv and Treatment Of Oropharyngeal Cancermentioning
confidence: 99%
“…42,43,50 The ECOG-ACRIN phase II E1308 trial, in which patients with stage III-IV HPV16 and/or p16-positive oropharyngeal cancer (N=80) received induction chemotherapy followed by reduced-dose RT and weekly cetuximab, recently reported results showing that RT deintensification may result in equivalent or similar responses in selected patients compared with fulldose RT. 51 The relationship between HPV and other prognostic or predictive factors such as smoking history and stage has been investigated. 52,53 For example, analyses of patients with oropharyngeal cancer who were enrolled in RTOG 9003 or 0129 (n=165) showed that smoking was associated with decreased OS and PFS, regardless of p16 status.…”
Section: Hpv and Treatment Of Oropharyngeal Cancermentioning
confidence: 99%
“…The 2-year overall survival with a total dose of 54 Gy and concurrent cetuximab was 94%. 19 The current study has several important limitations. A short follow-up and small sample size prevented us from making conclusions with regard to the effect of PDCRT on long-term clinical outcomes.…”
Section: Advances In Radiation Oncology: January-march 2018mentioning
confidence: 89%
“…In a prospective trial of lowrisk HPV + patients (T1-3 N0-N2b), 3 cycles of induction chemotherapy with cisplatin, paclitaxel, and cetuximab achieved an excellent complete clinical response (cCR) rate of 70%, which subsequently enabled them to be treated with a substantially lower dose of radiation (54Gy vs. 69. 3Gy) [36]. In fact, the benefit of chemotherapy is unclear in this selected group of low-risk patients and efforts are underway to evaluate if chemotherapy can be omitted altogether ( [35] and clinical trial NCT02254278).…”
Section: Discussionmentioning
confidence: 99%